CHALLENGES OF ECONOMIC DIPLOMACY POST-WTO DECISION IN THE PERSPECTIVE OF NATIONAL INTEREST ON INDONESIA'S NICKEL ORE EXPORT BAN POLICY TO THE EUROPEAN UNION - Oktaria Mawarni (Budi Luhur Journal of Strategic & Global Studies, 2025)
Abstract: This study examines Indonesia's nickel downstream policy as an effort to enhance the added value of natural resources, particularly nickel. With its vast nickel reserves, Indonesia has implemented an export ban on nickel ore to encourage the production of refined nickel products, aiming to sustainably increase state revenues. However, the implementation of this policy faces several challenges, including a legal dispute with the European Union and a World Trade Organization (WTO) ruling. WTO deemed the policy a violation of free trade principles, alongside issues such as dependency on foreign labor and environmental concerns. This study recommends strengthening economic diplomacy, developing local technology, and improving the skills of the domestic workforce to achieve independence and sustainability in Indonesia's nickel management.   Abstrak: Penelitian ini menyoroti mengenai kebijakan hilirisasi nikel di Indonesia sebagai upaya untuk meningkatkan nilai tambah sumber daya alam khususnya nikel. Indonesia yang memiliki cadangan tambang tersebut menerapkan larangan ekspor bijih nikel untuk mendorong produksi barang olahan nikel untuk meningkatkan pendapatan negara secara keberlanjutan. Indonesia dalam implementasi kebijakannya mendapatkan tantangan termasuk adanya gugatan Uni Eropa serta adanya putusan World Trade Organization (WTO). WTO menjatuhkan gugatan yang berisi pelanggaran prinsip perdagangan bebas, ketergantungan pada tenaga kerja asing, dan isu lingkungan. Penelitian ini merekomendasikan penguatan diplomasi ekonomi, pengembangan teknologi lokal, dan peningkatan keterampilan tenaga kerja domestik untuk mencapai kemandirian dan keberlanjutan pengelolaan nikel Indonesia.